2022
DOI: 10.1371/journal.pone.0275737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different amoxicillin treatment durations on microbiome diversity and composition in the gut

Abstract: Antibiotics seize an effect on bacterial composition and diversity and have been demonstrated to induce disruptions on gut microbiomes. This may have implications for human health and wellbeing, and an increasing number of studies suggest a link between the gut microbiome and several diseases. Hence, reducing antibiotic treatments may be beneficial for human health status. Further, antimicrobial resistance (AMR) is an increasing global problem that can be counteracted by limiting the usage of antibiotics. Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 94 publications
2
10
0
1
Order By: Relevance
“…Our findings show a significant association between antibiotic use and reduced overall survival in patients with HCC and Child–Pugh class A cirrhosis undergoing ICI treatment. This finding aligns with growing evidence suggesting the gut microbiota, which can be influenced by Ceftriaxone [ 30 ], Ciprofloxacin [ 31 ], Pipracillin/tazobactam [ 32 ], Meropenem [ 33 ], Augmentin [ 34 ], and Moxifloxacin [ 35 ] antibiotics used in our cohort, as indicated in Table 2 , significantly play a crucial role in regulating response to ICIs [ 23 , 36 ]. Furthermore, no differences in the overall survival in patients with HCC and Child–Pugh class B cirrhosis undergoing ICI treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings show a significant association between antibiotic use and reduced overall survival in patients with HCC and Child–Pugh class A cirrhosis undergoing ICI treatment. This finding aligns with growing evidence suggesting the gut microbiota, which can be influenced by Ceftriaxone [ 30 ], Ciprofloxacin [ 31 ], Pipracillin/tazobactam [ 32 ], Meropenem [ 33 ], Augmentin [ 34 ], and Moxifloxacin [ 35 ] antibiotics used in our cohort, as indicated in Table 2 , significantly play a crucial role in regulating response to ICIs [ 23 , 36 ]. Furthermore, no differences in the overall survival in patients with HCC and Child–Pugh class B cirrhosis undergoing ICI treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Augmentin [34], and Moxifloxacin [35] antibiotics used in our cohort, as indicated in Table 2, significantly play a crucial role in regulating response to ICIs [23,36]. Furthermore, no differences in the overall survival in patients with HCC and Child-Pugh class B cirrhosis undergoing ICI treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Our study corroborates with these findings, as there was no difference alpha diversity between severe/critical and asymptomatic COVID-19 when confounding by use of antimicrobial was removed. These results are consistent with animal and human non–COVID-19 studies that generally demonstrated that antimicrobial use reduces bacterial alpha diversity ( Huang et al., 2022 ; Kwon et al., 2022 ; Lekang et al., 2022 ). However, exclusion or statistical adjustment of samples for antimicrobial use was often not done or reported in COVID-19–related microbiome studies ( Ma et al., 2021 ; Merenstein et al., 2021 ; Rueca et al., 2021 ; Ventero et al., 2021 ; Chen et al., 2022 ; Gauthier et al., 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…So-called broad-spectrum antimicrobials are known to cause a loss of taxonomic richness and diversity during intake, followed by a long time to restore bacterial homeostasis. A study of mouse microbiota after amoxicillin treatment for 0, 3, 7 or 14 days shows this to be the case, with the greatest impact in the 14-day treatment group [4]. Interestingly, this study demonstrated that the shortest treatment (3 days) produced longer lasting microbiome effects in some bacterial taxa for several weeks.…”
Section: Antimicrobial Effects On the Gut Microbiomementioning
confidence: 74%